Recurrent Incisional Hernia Repair—An Overview - Köckerling, Ferdinand (Frontiers in Surgery, 2019)
Introduction: Recurrent incisional hernias with a rate of around 20% account for a relatively large proportion of all incisional hernias. It is difficult to issue any binding recommendations on optimum treatment in view of the relatively few studies available on this topic. This review now aims to collate the data available on recurrent incisional hernia. Material and Methods: A systematic search of the available literature was performed in January 2019 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library, as well as a search of relevant journals and reference lists. For the present analysis, 47 publications were identified as relevant. Results: There are mainly case series available on the treatment of recurrent incisional hernia. Eight evaluable case series and two prospective comparative studies report on treatment of between 27 and 85 recurrent hernias. After primary open repair of incisional hernia and defect sizes of < 8–10 cm, the recurrence operation can be performed in laparoscopic technique provided the surgeon has sufficient experience in that procedure. That also applies to multiple recurrences after exclusively open repair. There are no evaluable data on a repeat laparoscopic approach after minimally invasive repair of primary incisional hernia. Such an approach should only be chosen by very experienced laparoscopic surgeons and based on a well-founded indication. Further data are urgently needed on treatment of recurrent incisional hernia. Conclusion: Very little data are available on the treatment of recurrent incisional hernia. Based on the tailored approach concept, a laparoscopic approach undertaken by an experienced laparoscopic surgeon can be recommended for recurrent hernias after primary open repair and for defects of up to 8–10 cm.